Interactions between teacher unions and state in the Province of Buenos Aires during the 2000-2007 period - Mulcahy, Annie (Education Policy Analysis Archives, 2014)
This is a study of teacher union militancy in the Province of Buenos Aires during the 2000-2007 period. After a decade of educational reform, and within a new economic and political context, it analyzes the interactions between the major teacher unions –Sindicato Único de Trabajadores de la Educación de la Provincia de Buenos Aires (SUTEBA) and Federación de Educadores Bonaerenses (FEB)– and the governmental authorities of the Province. In order to create a map of teacher union militancy, in-depth interviews to main union and government actors were carried out, as well as a thorough analysis of news articles, union meeting records, and other research on the subject. The gathered information enables the inference of changes in strategies adopted by the actors throughout the period. The influence of external factors (changes in economic conditions, the relationship between the national and provincial levels of government) and those associated to union organizations (political identities, the construction of union alliances, their participation in different arenas and changes in political leaderships) gave way to an increase or decrease of teacher union militancy level, while impacting on their behaviour.